Construction method of secondary ion battery energy storage model device suitable for surface characterization

The preparation of V2O5 film electrodes through magnetron sputtering solves the uncertainty of characterization caused by the particle stacking structure and impurity composition in the secondary ion battery electrode, and achieves a more accurate study on the charging and discharging mechanism of active materials.

CN119650563AActive Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311197210.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

During the preparation of existing secondary ion battery electrodes, the stacking structure of active material particles and the composition of complex elements formed lead to uncertainty in characterization objects, affecting the accuracy of the charging and discharging mechanism of active materials.

Method used

The V2O5 film electrode is prepared by magnetron sputtering to form a regular film structure, avoiding the presence of particle stacking structure and impurity components, and ensuring the conductivity of the working electrode through electrode clamps.

Benefits of technology

The electrode components are single, no binder and conductive carbon impurities are achieved. The active material plays the charging and discharge function in the form of a regular surface film. The test results are more accurate, avoiding interference from adsorbed impurities between particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650563A_ABST
    Figure CN119650563A_ABST
Patent Text Reader

Abstract

The invention discloses a construction method of a secondary ion battery energy storage model device suitable for surface characterization, which comprises the following steps: covering one end of a conductive substrate with a shielding layer, vacuumizing a magnetron sputtering chamber at the magnetron sputtering temperature of 395 DEG C and the vacuum degree of 1-5Pa, preparing a V2O5 film electrode at the sputtering power of 30-300W, and removing the shielding layer to obtain the secondary ion battery energy storage model device suitable for surface characterization. And clamping the conductive substrate of which the film electrode is not covered by the V2O5 layer by using an electrode clamp to ensure that the working electrode can be conductively connected with an external electrochemical workstation, thereby completing the assembly of the secondary ion battery energy storage model battery device. The thin film electrode prepared in the magnetron sputtering mode is single in component and regular in structure, the test result is information of the real state of the reaction active material, interference of impurities adsorbed among particles does not exist, and the result is more accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage technology, and in particular to a method for constructing a secondary ion battery energy storage model device suitable for surface characterization. Background Art

[0002] Electrochemical energy storage technology (especially various secondary chemical batteries, etc.) has the advantages of small geographical constraints, flexible and easy to adjust energy storage scale, and fast response speed, and has attracted widespread attention from emerging markets and scientific research fields. The development of advanced secondary battery technology will play an important role in applications such as renewable energy grid connection, grid peak shaving and valley filling, and electric vehicles. It is also of great significance to future energy transformation and environmental protection. Among the many secondary battery technologies, secondary ion batteries have broad prospects. For example, lithium-ion batteries have achieved great commercial success, and sodium-ion batteries, zinc-ion batteries, etc. have also been booming. However, due to the stringent requirements of characterization methods on samples, research on the energy storage mechanism of electrode materials has been challenged, hindering the further development of secondary ion batteries.

[0003] The traditional preparation process of secondary ion battery electrodes is as follows: Figure 1 As shown: Grind the conductive carbon and active material in a certain proportion and add them to a solution containing a polymer. After stirring, apply them on the metal current collector with a scraper. After drying, cut them into a certain size to obtain an electrode sheet. This preparation method inevitably forms a stacking structure of active material particles. After assembling the battery, impurities such as electrolyte are easily adsorbed between the active material particles. For surface-sensitive technologies such as X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (TOF-SIMS), they are very easily affected by surface contamination. When studying the charge and discharge mechanism of active materials, the accuracy of the test results is easily interfered by these impurity components. Summary of the invention

[0004] In order to avoid the uncertainty of the characterization object caused by factors such as the complex particle stacking structure and elemental composition in the electrodes of traditional secondary ion batteries, the present invention provides a method for constructing a secondary ion battery energy storage model device suitable for surface characterization, thereby constructing a model battery for testing and analysis.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for constructing a secondary ion battery energy storage model device suitable for surface characterization, the method comprising the following steps:

[0007] (1) Covering one end of the conductive substrate with a shielding layer, fixing the conductive substrate on a sample stage, placing a metal vanadium target in a magnetron sputtering vacuum chamber, and evacuating the magnetron sputtering chamber;

[0008] (2) Raise the sample plate temperature to 395°C and maintain it for 3-20 minutes, and turn on the sample plate rotation;

[0009] (3) introducing working gas, fixing the working gas flow rate and adjusting the gas pressure to a predetermined working gas pressure;

[0010] (4) Pre-sputtering to remove impurities on the target surface;

[0011] (5) maintaining the working gas flow rate, adjusting the vacuum degree to 1-5 Pa, maintaining the sputtering power at 30-300 W for 10-200 minutes, setting the bias voltage to 50 V, and keeping the sample baffle open, cooling to room temperature, and obtaining a V2O5 thin film electrode;

[0012] (6) Remove the shielding layer, use the thin film electrode prepared in step (5) as the working electrode, and the negative electrode zinc foil as the counter electrode. Due to the shielding layer covering, one end of the conductive substrate is not covered by the V2O5 layer. Use an electrode clamp to clamp the conductive substrate of the thin film electrode that is not covered by the V2O5 layer to ensure that the working electrode can be conductively connected to the external electrochemical workstation. Use an electrode clamp to clamp the negative electrode, and immerse the two electrodes in an aqueous electrolyte solution with a distance of 0.5-3 cm between the two electrodes. The metal columns at the upper ends of the two electrode clamps are respectively connected to the corresponding wires of the electrochemical workstation, and the reference electrode wire is connected to the counter electrode to complete the assembly of the secondary ion battery energy storage model device.

[0013] In the above technical solution, further, in the step (1), the conductive substrate comprises any one of a graphite sheet with a smooth surface, a glassy carbon electrode sheet, and a silicon sheet with a metal plated surface;

[0014] The vacuum degree is 1.0×10 -3 Pa;

[0015] The shielding layer is made of a metal sheet or Kapton tape that can withstand a high temperature of 395 degrees Celsius.

[0016] In the above technical solution, further, in the step (2), the heating rate is 3-25°C / min, preferably 10°C / min;

[0017] The sample plate rotation speed is 10 revolutions / min.

[0018] In the above technical solution, further, in the step (3), the Ar flow rate is adjusted to 60-90Sccm, the O2 flow rate is 5-20Sccm, preferably the Ar flow rate is 90Sccm, and the O2 flow rate is 10Sccm; the pressure control vacuum degree is 1-5Pa, preferably 3Pa.

[0019] In the above technical solution, further, in the step (4), the sputtering power is maintained at 30-200 W for 0.5-5 minutes, preferably at 100 W for 3 minutes, and the sample baffle is kept closed to remove contaminants on the target surface.

[0020] In the above technical solution, further, in the step (5), the vacuum degree is adjusted to 2Pa and maintained at a sputtering power of 200W for 60 minutes.

[0021] In the above technical solution, further, in the step (6), the thickness of the thin film electrode is 20-200nm, and preferably 100nm by controlling the sputtering time. If the thickness is less than 20nm, the vanadium oxide layer of the working electrode is easily dissolved and eroded by the electrolyte. When the thickness is greater than 200nm, zinc ions are embedded in the vanadium oxide layer after discharge, which easily causes it to fall off from the substrate, and normal charging and discharging and subsequent characterization work cannot be performed.

[0022] The beneficial effects of the present invention are:

[0023] Compared with the traditional method of directly using complex stacked structure electrodes to study the charging and discharging mechanism of active materials, the thin film electrode prepared by magnetron sputtering in the present invention has a single component and does not contain impurity components such as binders and conductive carbon. The active material performs the charging and discharging function in the form of a regular surface film. It only needs to clean the surface of the adsorbed electrolyte and other impurities through argon etching, ion beam polishing, etc. The test result is the information on the true state of the reactive active material. There is no interference from impurities adsorbed between particles, and the result is more accurate.

[0024] When assembling the model device, an electrolytic cell structure is used, and the working electrode and the counter electrode are directly inserted into the electrolyte with a distance of 0.5-3 cm between the two electrodes. The separator used in traditional actual batteries such as button batteries, laminated batteries or wound batteries is not required. This can avoid damage to the vanadium oxide layer caused by mechanical stress when the battery is disassembled after charging and discharging in the actual battery, and obtain samples with complete vanadium oxide layers at different stages, which is conducive to subsequent characterization. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 Schematic diagram of the traditional preparation process of secondary ion battery electrodes;

[0027] Figure 2This is a schematic diagram of the process of preparing V2O5 thin film electrodes by magnetron sputtering in Example 1;

[0028] Figure 3 is a surface morphology image of the V2O5 layer on the thin film electrode surface obtained by magnetron sputtering in Example 1 measured by AFM; a is a surface morphology image of the gold substrate and the V2O5 layer on the thin film electrode surface measured by AFM, and b is the thickness of the V2O5 layer on the gold substrate obtained after data processing of Figure a, i.e., the thickness of the V2O5 layer;

[0029] Figure 4 The Raman spectra of V2O5 prepared by magnetron sputtering in Example 1 are compared with those of commercial V2O5;

[0030] Figure 5 This is a schematic diagram of a thin film electrode assembly model device of Example 1;

[0031] Figure 6 The CV curves of the model device assembled with thin film electrodes and the actual battery of Example 1, a is the model battery assembled with thin film electrodes, and b is the CV curve of the actual battery;

[0032] Figure 7 The in-situ Raman spectra of the model device assembled with the thin film electrode and the actual battery during the charge and discharge process of Example 1, a is the in-situ Raman spectrum of the model battery assembled with the thin film electrode during the charge and discharge process, and b is the in-situ Raman spectrum of the actual battery during the charge and discharge process;

[0033] Figure 8 The Raman spectra of V2O5 prepared in Example 1 and Comparative Example 1 are compared with those of commercial V2O5. DETAILED DESCRIPTION

[0034] The following examples may enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0035] Example 1

[0036] This embodiment takes the V2O5 positive electrode for zinc ion battery as an example, and the preparation process of the thin film electrode is as follows: Figure 2 As shown. Since V2O5 is a semiconductor material with poor conductivity, in order to ensure that the battery can be charged and discharged normally and minimize the contact resistance of the battery, a layer of V2O5 with a thickness of about 100nm is sputtered on the gold layer substrate of the conductive substrate (gold-plated silicon wafer) by magnetron sputtering, and the sputtering mode adopts DC sputtering. In this embodiment, the purity of the vanadium target material is 99.999%, the diameter of the target material is 50.8mm, and the thickness is 3mm. Specifically: Use high-temperature resistant Kapton tape to cover part of the gold layer at one end of the gold-plated silicon wafer, fix the gold-plated silicon wafer on the sample stage, put the metal vanadium target material into the magnetron sputtering vacuum chamber, and roughly evacuate to a vacuum degree of 1.0×10 -3Pa, and then raise the temperature of the sample plate to 395°C at a heating rate of 10°C per minute, and maintain it for 10 minutes. At this time, the sample plate rotates at 10 turns per minute; then adjust the Ar flow rate to 90Sccm, the O2 flow rate to 10Sccm, and the pressure control vacuum to 3Pa; maintain it for 3 minutes at a sputtering power of 100W, and keep the sample baffle closed. This step is to remove contaminants on the surface of the target; maintain the above-mentioned air inlet flow rate, adjust the vacuum to 2Pa, the sputtering power to 200W, set the bias voltage to 50V, open the sample baffle, sputter under this condition for 60 minutes, cool to room temperature, and take out the thin film electrode for use.

[0037] like Figure 3 As shown, Figure 3 a is the surface morphology of the gold substrate and V2O5 layer on the thin film electrode surface measured by AFM, from which the thickness of the V2O5 layer on the gold substrate is 100nm. According to the data processing of this figure, Figure 3 b, the thickness of the V2O5 layer.

[0038] Raman detection of the sputtered thin layer shows the same spectrum as commercial V2O5 ( Figure 4 ), indicating that the regular thin layer obtained by sputtering is V2O5. The model electrode thus prepared has a regular thin film structure with flat top and bottom. As long as its surface is cleaned, a signal without surface pollution can be obtained, which more truly reflects the information of the measured sample.

[0039] The Kapton tape shielding layer was removed, and the V2O5 thin film electrode prepared by magnetron sputtering was used as the working electrode, the zinc metal sheet was used as the counter electrode, the distance between the two electrodes was 0.5-3cm, and a 3M Zn(OTf)2 aqueous solution was used as the electrolyte to assemble a model battery, such as Figure 5 As shown. Specifically, use an electrode clamp to clamp the gold layer on the top of the thin film electrode that is not completely covered by the V2O5 layer to ensure that the working electrode can be electrically connected to the external electrochemical workstation. Use an electrode clamp to clamp the zinc sheet on the counter electrode. Immerse the two electrodes in a 3M Zn(OTf)2 aqueous solution. The metal columns on the top of the two electrode clamps are connected to the corresponding wires of the electrochemical workstation, and the reference electrode wire is connected to the counter electrode. At this time, the assembly of the model battery is completed and it can be charged and discharged through the electrochemical workstation. -1 The cyclic voltammetry curve at a scan rate of Figure 6 As shown in the figure, the CV curve of the actual battery has two pairs of typical redox peaks, corresponding to the V generated by the insertion and extraction process of zinc ions in the V2O5 electrode. 4+ / V 3+ and V 5+ / V 4 + Reaction, in situ Raman spectroscopy characterization of the battery charging and discharging process ( Figure 7), and found that the spectrum change patterns of the model battery and the actual battery were consistent, indicating that the model battery and the actual battery have consistent electrochemical behaviors. The electrodes obtained from the model battery can be used for subsequent characterization to study the charge and discharge mechanism of the electrode and obtain accurate information without interference from pollutants.

[0040] At the same time, the present invention is not limited to the V2O5 material in this embodiment. Any electrode material that is easy to prepare into a uniform and flat thin layer structure in a secondary battery can adopt the above-mentioned construction method when studying its charge storage mechanism to avoid the problem of inaccurate test results caused by impurity interference; in the process of preparing thin film electrodes, it is not limited to the use of magnetron sputtering, and other means that can produce regular thin film structures, such as atomic layer deposition, chemical vapor deposition, molecular beam epitaxial growth, etc., can be used in the method of preparing thin film electrodes.

[0041] Comparative Example 1

[0042] The difference from Example 1 is that the magnetron sputtering temperature is room temperature.

[0043] The Raman spectrum of the model electrode prepared in Comparative Example 1 is compared with the Raman spectrum of Example 1. Figure 8 As shown, the film obtained by magnetron sputtering at room temperature has no Raman peak, indicating that the sputtered film obtained under this condition is not V2O5, and therefore cannot be used for subsequent battery assembly.

[0044] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for constructing a secondary ion battery energy storage model device suitable for surface characterization, characterized in that: The method comprises the following steps: (1) Covering one end of the conductive substrate with a shielding layer, fixing the conductive substrate on a sample stage, placing a metal vanadium target in a magnetron sputtering vacuum chamber, and evacuating the magnetron sputtering chamber; (2) Raise the sample plate temperature to 395°C and maintain it for 3-20 minutes, and turn on the sample plate rotation; (3) introducing working gas, fixing the working gas flow rate and adjusting the gas pressure to a predetermined working gas pressure; (4) Pre-sputtering to remove impurities on the target surface; (5) maintaining the working gas flow rate, adjusting the vacuum degree to 1-5 Pa, maintaining the sputtering power at 30-300 W for 10-200 minutes, setting the bias voltage to 50 V, and keeping the sample baffle open, cooling to room temperature, and obtaining a V2O5 thin film electrode; (6) Remove the shielding layer, use the thin film electrode prepared in step (5) as the working electrode, and the negative electrode as the counter electrode. Use an electrode clamp to clamp the conductive substrate of the thin film electrode that is not covered by the V2O5 layer to ensure that the working electrode can be electrically connected to the external electrochemical workstation. Use an electrode clamp to clamp the negative electrode, and the distance between the two electrodes is 0.5-3cm. Immerse the two electrodes in an aqueous electrolyte solution, and connect the metal columns at the upper ends of the two electrode clamps to the corresponding wires of the electrochemical workstation respectively. The reference electrode wire is connected to the counter electrode to complete the assembly of the secondary ion battery energy storage model battery device.

2. The construction method according to claim 1, characterized in that: In the step (1), the conductive substrate includes any one of a graphite sheet with a smooth surface, a glassy carbon electrode sheet, and a silicon sheet with a metal plated surface; The vacuum degree is 1.0×10 -3 Pa; The shielding layer is made of metal sheet or Kapton tape.

3. The construction method according to claim 1, characterized in that: In the step (2), the heating rate is 3-25°C / min; The sample plate rotation speed is 10 revolutions / min.

4. The construction method according to claim 1, characterized in that: In the step (3), the Ar flow rate is adjusted to 60-90 Sccm, the O2 flow rate is adjusted to 5-20 Sccm, and the pressure vacuum is controlled to 1-5 Pa.

5. The construction method according to claim 1, characterized in that: In the step (4), the sputtering power is maintained at 30-200 W for 0.5-5 minutes, and the sample baffle is kept closed.

6. The construction method according to claim 1, characterized in that: In the step (6), the thickness of the thin film electrode is 20-200 nm.

Citation Information

Patent Citations

  • V2ON cathode material for lithium ion cells and preparing method thereof

    CN101872855A

  • Magnetron sputtering preparation method of vanadium oxide

    CN104213087A

  • A 3D thin film negative electrode of all-solid-state thin film lithium ion battery and a preparation method thereof

    CN109167061A

  • Positive pole piece, preparation method thereof and battery

    CN116014062A

  • Preparation method of zinc ion battery negative electrode material with three-dimensional structure

    CN116314690A